Co-relation of ASA-PS with post operative complications and morbidity in hysterectomy patients - Nijhawan, Dushyant M.; Upadhye, Jayshree J. (International Journal of Research in Medical Sciences, 2018)
Background: Today, ASA grading is done for any surgical case performed under anesthesia. ASA PS is significantly associated with post-operative morbidity and mortality. For gynecologists, hysterectomy is the most common operation performed by gynecologists, next to caesarean section. The primary focus of this study was to review the ASA-PS of hysterectomy patients. Methods: This retrospective study was performed in the department of Anesthesiology, in collaboration with Department of Obstetrics and gynecology. All women who underwent hysterectomy were included in this study. Results: In this study, out of 100 patients, clinical indication was fibroid in 45 (45%) patients, menorrhagia in 15 (15%) patients, adenomyosis in 25 (25%) patients, uterovaginal prolapse in 5 (5%) patients, endometrial polyp in 5 (5%) patients and ovarian tumor in 5 (5%) patients. ASA-PS grade 1 was seen in 65 (65%) of patients, 25 (25%) of patients had ASA-PS grade 2, 10 (10%) of patients had ASA-PS grade 3 while none of the patients had ASA-PS grade 4 and 5. 4 (4%) patients had urinary tract infection, 2 (2%) patients had deep vein thrombosis, 1 (1%) patient had myocardial infarction and 1 (1%) patients had pneumonia. 25 (25%) patients were obese, 24 (24%) patients had diabetes, 20 (20%) patients had hypertension requiring treatment and 6 (6%) patients had wound infection. Conclusions: ASA PS has strong, independent association with post-operative medical complications. This along with its simplicity, makes it a valuable prognostic metric.